2012
DOI: 10.1007/s00424-012-1078-y
|View full text |Cite
|
Sign up to set email alerts
|

TRPV1 activation prevents nonalcoholic fatty liver through UCP2 upregulation in mice

Abstract: Nonalcoholic fatty liver is characterized by the fatty deformation and lipid deposition of hepatic parenchymal cells that are associated with cardiometabolic diseases. In this study, we report the effect of capsaicin on its receptor, transient receptor potential vanilloid 1 (TRPV1) cation channel, in preventing fatty liver formation. Functional TRPV1 has been detected in hepatocytes and liver tissues. TRPV1 activation by capsaicin reduced lipid accumulation and triglyceride level in the liver from wild-type (W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
52
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(66 citation statements)
references
References 25 publications
(29 reference statements)
3
52
0
1
Order By: Relevance
“…A previous study also showed that dietary capsaicin significantly decreased triglyceride levels in the plasma and/or liver, as well as the expression of inflammatory adipocytokine genes (e.g., monocyte chemoattractant protein-1 and interleukin-6) and macrophage infiltration [11]. The capsaicin-induced TRPV1 activation promoted lipolysis of visceral fat, and reduced triglyceride level via upregulation of hepatic uncoupling protein 2 (UCP2) [51]. …”
Section: Discussionmentioning
confidence: 99%
“…A previous study also showed that dietary capsaicin significantly decreased triglyceride levels in the plasma and/or liver, as well as the expression of inflammatory adipocytokine genes (e.g., monocyte chemoattractant protein-1 and interleukin-6) and macrophage infiltration [11]. The capsaicin-induced TRPV1 activation promoted lipolysis of visceral fat, and reduced triglyceride level via upregulation of hepatic uncoupling protein 2 (UCP2) [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Recently, Li et al reported that transient receptor potential vanilloid 1 (TRPV1) activation by capsaicin reduced lipid accumulation and TG levels in mice, and chronic dietary capsaicin increased the hepatic uncoupling protein 2 expression. 26) As an alternative mechanism it would be interesting to test whether eugenol activates TRPV1 cation channel in hepatocytes, because eugenol belongs to a vanilloid compound and natural congener of capsaicin. TRPV1 is affiliated to the family of nonselective cation channels that display high Ca 2+ permeability.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, appropriate amounts of dietary capsaicin have beneficial effects on obesity and NAFLD[63,64]. A survey indicated that dietary capsaicin could reduce lipid accumulation and triglyceride levels in mice fed with a high-fat diet by up-regulating the levels of uncoupling protein 2 (UCP2)[64].…”
Section: Role Of Autophagy Induced By Traditional Chinese Herbal Extrmentioning
confidence: 99%
“…A survey indicated that dietary capsaicin could reduce lipid accumulation and triglyceride levels in mice fed with a high-fat diet by up-regulating the levels of uncoupling protein 2 (UCP2)[64]. UCP2 was thought to play an important role in mitochondrial lipolysis and oxidative stress.…”
Section: Role Of Autophagy Induced By Traditional Chinese Herbal Extrmentioning
confidence: 99%